Exploration of Fruit Fly Species (Bactrocera spp.) in Cayenne pepper (Capsicum frutescens L.) Orchards at Agro Techno Center (ATC) - Weri Herlin; Samuel Gilbert Damanik; Oktaviani Oktaviani (Journal of Global Sustainable Agriculture, 2026)
Studies on the population and species composition of fruit flies on bird's eye chili plants are still needed to support more effective control efforts. This study aimed to examine the population abundance and species diversity of fruit flies (Bactrocera spp.) associated with bird's eye chili (Capsicum frutescens L.) and to identify the most effective trapping method at the Experimental Garden of the Faculty of Agriculture, Sriwijaya University. Observations were conducted over eight weeks using various trapping methods, with parameters including species diversity, species dominance, and species evenness. The data obtained were analyzed using ANOVA followed by DMRT at the 5% significance level. The study successfully collected 6,689 fruit fly individuals representing three species: Bactrocera dorsalis, B. carambolae, and B. umbrosa. B. dorsalis was the most abundant species, accounting for 4,474 individuals (67%) across all trapping methods, followed by B. carambolae (1,607 individuals) and B. umbrosa (608 individuals). Analysis of variance and DMRT (5%) revealed significant differences among trap types: the Yellow Sticky Trap yielded the highest catch, with an average of 206 individuals per week, compared to the Methyl Eugenol Trap (70 individuals per week) and the sweep net (2 individuals per week). These results indicate that the Yellow Sticky Trap has the potential to serve as a key component in environmentally friendly fruit fly monitoring and control strategies for bird's eye chili cultivation. Consequently, the use of Yellow Sticky Traps could be a valuable component of eco-friendly fruit fly management strategies in horticultural cultivation systems.